Influence of occupational safety culture on the occupational risk level in the organization - Saik, Pavlo; Tsopa, Vitalii; Koriashkina, Larysa; Cheberiachko, Serhii; Deryugin, Oleg; Lozynskyi, Vasyl (Frontiers in Public Health, 2025)
IntroductionThis study aims to develop a methodology for assessing the risk of hazardous situations, incidents, and related events, with consideration of the level of “occupational safety culture” among employees within an organization.MethodsThe research employs a systematic approach, incorporating mathematical and simulation modeling to evaluate the influence of safety culture on occupational risk levels.ResultsA methodology has been developed to assess the safety culture level and its impact on the likelihood of hazardous events. This methodology is considering based on the degree of compliance with Occupational Safety and Health Management Systems (OHSMS) requirements by employees, categorized into five stages of safety culture: (1) indifference, (2) response, (3) dependence, (4) independence, and (5) interdependence. Key factors influencing each stage have been identified. The model demonstrates that employees’ compliance with OHSMS requirements is shaped by the roles of managers, safety professionals, and employees within a systemic and social interaction framework.DiscussionThe proposed model enhances the occupational risk management process by incorporating safety culture as a key factor. It establishes a correlation between the level of safety culture and the risk of incidents at different development stages. The model also highlights how initial compliance levels, awareness of safety requirements, and peer and managerial influence affect risk outcomes. Furthermore, it identifies three primary causes underlying non-compliance: negligence, lack of competence (due to insufficient training), and selfish motives.